Self-employed and stressed out? The impact of stress and stress management on entrepreneurs’ mental health and performance - Kiefl, Sophia; Fischer, Sophie; Schmitt, Jan (Frontiers in Psychology, 2024)
Entrepreneurs play a decisive role in economic and social stability. However, the start-up rate in Germany has fallen over the past decade, possibly due to the stress associated with entrepreneurial activities. Stressors such as financial uncertainty and time pressure are common among entrepreneurs and have a negative impact on their mental well-being. Nevertheless, research on stress management strategies among self-employed individuals is still limited. This pilot study presents the results of a quantitative analysis with 117 self-employed participants in Germany, focusing on typical entrepreneurial work demands and selected stress coping mechanisms. The analysis revealed a significant correlation between quantitative demands and mental exhaustion. Additionally, a high positive correlation between presenteeism and workload suggests that presenteeism may play a partial role in explaining the variance in workload. These results illustrate how high job demands can lead to self-endangering behaviors that negatively impact mental health. Although no significant moderating effect of proactive coping on the relationship between job demands and mental exhaustion was found, significant negative correlations between proactive coping and both job demands and mental exhaustion suggest a potential protective role of proactive coping against work-related stress. This study emphasizes the importance of understanding stress coping strategies in self-employed individuals and their impact on entrepreneurial success and mental well-being.